Risk factors associated with in-hospital mortality in critically ill elderly patients with venous thromboembolism - Puri, Anju; Giri, Mohan; Oli, Manoj; Zhao, Qinghua (International Journal of Research in Medical Sciences, 2024)
Background: Venous thromboembolism (VTE) is a major cause of morbidity and mortality for patients admitted to the intensive care unit (ICU). The present study aims to investigate the risk factors for in-hospital mortality among critically ill elderly patients with VTE. Methods: This was a retrospective cohort study utilizing data from the large medical information mart for intensive care IV (MIMIC-IV) database. All elderly patients diagnosed with VTE were included in the analysis. The analyses were conducted using SPSS version 26.0 software and MedCalc version 19.6. Univariable and multivariable logistic regression models were conducted to explore potential risk factors associated with in-hospital mortality. Results: The study population had a median age of 75 years, with a range from 69.0 to 82.0 years, and males represented 50.4% of the cohort. Among critically ill VTE patients, the in-hospital mortality rate was 18.5% (237 out of 1282). Multivariable regression analysis revealed that longer ICU stays [OR: 1.034; 95% CI: 1.010-1.059, p=0.005], higher Charlson comorbidity index (CCI) scores [OR: 1.090; 95% CI: 1.001-1.187, p=0.046], elevated simplified acute physiology score II (SAPS II scores) [OR: 1.039; 95% CI: 1.023-1.056, p<0.001], increased red blood cell distribution width (RDW) levels [OR: 1.088; 95% CI: 1.006-1.178, p=0.035], lower mean arterial pressure (MAP) [OR: 0.975; 95% CI: 0.957-0.994, p=0.011], presence of severe liver disease [OR: 2.036; 95% CI: 1.051-3.941, p=0.035], and the necessity for renal replacement therapy (RRT) [OR: 2.478; 95% CI: 1.315-4.671, p=0.005] were significantly associated with an increased risk of in-hospital mortality among elderly ICU patients with VTE. Conclusions: The study identifies numerous independent risk factors associated with in-hospital mortality among critically ill elderly patients with VT. These factors include prolonged length of ICU stay, elevated scores on the CCI and SAPS II, increased RDW, reduced MAP, the presence of severe liver disease, and the necessity for RRT.